Morphological state of the cerebral cortex in experimental traumatic brain injury against the activation and blockade of cholinergic systems - S. A. Khudoley; S. V. Ziablitsev (Морфологія, 2020)
Background. Central cholinergic systems play a key role in the adaptation of the central nervous system to traumatic brain injury. Objective – to establish the effect of cholinergic systems activation and blockade on the morphological state of the cerebral cortex in the acute period of traumatic brain injury. Methods. Trauma was simulated with a free fall of a load on fixed head of animal. To activate the cholinergic systems, choline alfoscerate (gliatilin, 6 mg/kg) was administered to rats before injury, and biperiden hydrochloride (akinetone; 0.6 mg/kg) was used for blocking. Histological and immunohistochemical studies were performed 3, 24, 48 and 72 hours after trauma. Sections of the cerebral cortex for light microscopy were stained with hematoxylin and eosin. For immunohistochemical studies, antibodies to neuron-specific enolase (NSE) and glial fibrillar acidic protein (GFAP) were used. Antibodies were visualized using a DAKO Poly Vue HRP/DAB polymer detection system. Light microscopy was performed on the Olimpus BX 40 microscope with the Olimpus C3030-ADU digital camera and Olimpus DP-Soft. Results. The activation of the cholinergic systems in the acute period led to a significant decrease in the lethality of experimental animals. At the same time, an increase of the normochromic neurons number and the synthesis of neuron-specific proteins: NSE and GFAP were noted in the cerebral cortex, which was a reflection of the full functioning of neurons and neuroglia. The cholinergic systems blockade was accompanied by high mortality and caused inhibition of the functional activity of neurons, the development of neurodestructive changes with a significant decrease in NSE-positive staining and GFAP activity, which reflected progressive disorders of neurons and astrocytic neuroglia. Conclusion. The results obtained confirmed the key role of central cholinergic systems for the implementation of the adaptive response in traumatic brain injury and showed the nature of morphological changes in the brain during their activation and blockade.